Interleukin-6 regulates the expression of hepatic canalicular efflux drug transporters after cecal ligation and puncture-induced sepsis: A comparison with lipopolysaccharide treatment. (1st February 2023) - Ashino, Takashi; Nakamura, Yuki; Ohtaki, Hirokazu; Iwakura, Yoichiro; Numazawa, Satoshi
Abstract: Hepatic multidrug transporters expressed on the canalicular membrane play a role in the hepatobiliary excretion of xenobiotics and endogenous substrates. The aim of this study was to elucidate the role of pro-inflammatory cytokines in the regulation of hepatic drug transporter expression after cecal ligation and puncture (CLP), a valuable tool for studying polymicrobial sepsis, and to compare CLP with lipopolysaccharide (LPS) treatment. CLP reduced the expression of Mdr2/Abcb4, Mrp2/Abcc2, Bsep/Abcb11, Bcrp/Abcg2, and Mate1/Slc47a1 mRNAs in wild-type (WT) mouse livers in a time-dependent manner up to 48 h postoperation. LPS also reduced the expression of all transporters in WT mouse livers 24 h posttreatment; thereafter, expression levels tended to return to normal by 48 h posttreatment. IL-6 −/− mice exhibited inhibited downregulation of drug transporters following CLP, although IL-1 −/− and TNFα −/− mice exhibited the reduced expression of all transporters in a manner similar to that found in WT mice. Compared with CLP, LPS treatment reduced the expression of all transporters in all cytokine-deficient mouse livers, except for the expression of Mrp2/Abcc2 in IL-6 −/− mice. Overall, these findings suggest that IL-6 is major factor in the downregulation of hepatic multidrug transporters following the onset of polymicrobial sepsis but not after LPS treatment. Graphical Abstract: ga1 Highlights: Cecal ligation and puncture-induced sepsis downregulate hepatic drug transporters. IL-6 is important for the downregulation of drug transporters following sepsis. Lipopolysaccharide downregulates hepatic drug transporters in IL-6-deficient mice.